Local Structure Analysis of Incommensurate Phase in Ti-42Ni-8Fe(at.%) Alloy by X-ray Fluorescence Holography. (2015) - Terai, T.; Toriyama, A.; Fukuda, T.; Kakeshita, T.; Hayashi, K.; Happo, N.; Hosokawa, S.
Abstract: We have investigated local structures around Ni and Fe atoms by X-ray fluorescence holography (XFH) method in incommensurate (IC) phase of Ti-42Ni-8Fe(at.%) alloy and obtained the results as the followings; (i) The atomic distances between Ni atom and Fe atom and those 2nd nearest neighbor atoms are 0.27 nm and 0.29 nm, respectively. (ii) The atomic image intensities of 1st nearest neighbor atoms around Fe atoms are much weaker than those around Ni atoms. These results indicate that nanometer-sized heterogeneous strain exists and it is the cause of nanometer-sized domain in IC phase.